Clinical Courses of IKAROS and CTLA4 Deficiencies: A Systematic Literature Review and Retrospective Longitudinal Study - Hoshino, Akihiro; Toyofuku, Etsushi; Mitsuiki, Noriko; Yamashita, Motoi; Okamoto, Keisuke; Yamamoto, Michio; Kanda, Kenji; Yamato, Genki; Keino, Dai; Yoshimoto-Suzuki, Yuri; Kamizono, Junji; Onoe, Yasuhiro; et al. (Frontiers in Immunology, 2022)
IKAROS and CTLA4 deficiencies are inborn errors of immunity and show similar clinical phenotypes, including hypogammaglobulinemia and autoimmune diseases (ADs). However, the differences in clinical features and pathogenesis of these are not fully understood. Therefore, we performed systematic literature reviews for IKAROS and CTLA4 deficiencies. The reviews suggested that patients with IKAROS deficiency develop AD earlier than hypogammaglobulinemia. However, no study assessed the detailed changes in clinical manifestations over time; this was likely due to the cross-sectional nature of the studies. Therefore, we conducted a retrospective longitudinal study on IKAROS and CTLA4 deficiencies in our cohort to evaluate the clinical course over time. In patients with IKAROS deficiency, AD and hypogammaglobulinemia often develop in that order, and AD often resolves before the onset of hypogammaglobulinemia; these observations were not found in patients with CTLA4 deficiency. Understanding this difference in the clinical course helps in the clinical management of both. Furthermore, our results suggest B- and T-cell-mediated ADs in patients with IKAROS and CTLA4 deficiencies, respectively.